Eksplorasi Nilai Filosofis dan Sistem Tukar Koin terhadap Aktivitas Jual Beli di Pasar Sarwono - Luluk Zakiatus Sholikhah; Abdullah Basar; Eka Zuliana (PT. PENERBIT TIGA MUTIARA, 2025)
This research examines the application of ethnomathematics in coin exchange activities at Sarwono Market, which is related to learning arithmetic operations, with the aim of understanding how everyday practices in market transactions can serve as a medium for learning mathematics. The method used in this study is a qualitative approach with an ethnographic perspective, allowing the researcher to observe and understand phenomena within a broader social context. Data collection was carried out through interviews with traders and market visitors, direct observation of the coin exchange activities, and documentation of activities related to these transactions. The collected data were then analyzed using three main stages: data reduction, data presentation, and conclusion drawing. The results of the study show that the practice of coin exchange not only facilitates transactions in the market but also serves as a medium for applying arithmetic operations in everyday life. This activity encourages the development of logical thinking skills, such as addition, subtraction, multiplication, and division, which are frequently used in the bargaining process or in determining the price of goods. Furthermore, coin exchange helps maintain price stability and increases transaction efficiency in the market by reducing dependence on paper money, which is often difficult to divide accurately. Thus, the study concludes that the application of ethnomathematics in coin exchange activities at Sarwono Market provides dual benefits, both in the economic context and in mathematics education.